Highly stretchable and durable fiber-shaped strain sensor with porous core-sheath structure for human motion monitoring. (22nd March 2020) - Yue, Xiaoyan; Jia, Yanyan; Wang, Xiaozheng; Zhou, Kangkang; Zhai, Wei; Zheng, Guoqiang; Dai, Kun; Mi, Liwei; Liu, Chuntai; Shen, Changyu
Abstract: The preparation of a satisfactory strain sensor integrated with ultrahigh sensitivity, large application range and superior stability is still a huge challenge. Herein, a highly stretchable carbon black/thermoplastic polyurethane fibrous strain sensor with porous and core-sheath structure is successfully prepared via an efficient coaxial wet-spun approach. The fiber possesses a porous monolith structure owing to countercurrent diffusion of the solvent and coagulation. An ultrahigh sensitivity (maximum gauge factor of 28, 084), fast response time (200 ms), favorable durability (>11, 000 cycles) and large strain range (>200%) are achieved simultaneously. Intriguingly, the values of ln (R/R0 ) of the fiber show a good linearity versus tensile strain, which can be used to predict changes of sensitivity in application. The tunneling theory is employed to analyze the response behaviors. The fibrous strain sensor is then utilized for detecting various human movements and tactile sensing, proving its tremendous potential as wearable electronics. Graphical abstract: Image 1